Chloroplast Genome Sequence of Lagerstroemia guilinensis (Lythraceae, Myrtales), a Species Endemic to the Guilin Limestone Area in Guangxi Province, China - Gu, Cuihua (Genome Announc, 2016)
We announce here the first complete chloroplast genome sequence of Lagerstroemia guilinensis (Lythraceae, Myrtales), a species endemic to the Guilin limestone area, along with its genome structure and functional gene annotations. The plant was collected from Guilin, Guangxi, China, and deposited as a germplasm accession of the Zhejiang Agriculture and Forestry University Collection (ZAFU 1507144). This genome will provide valuable information for future research of the Lagerstroemia genus and its relatives.